PENERAPAN METODE GROUP INVESTIGATION DALAM PEMBELAJARAN PAI KELAS X SMK KARYA GUNA 1 BEKASI - Farahiyah Azzyati; Laela Apri Liani (BADAN PENERBIT STIEPARI PRESS, 2023)
The duty of a teacher is to provide broad insight to his students. To help and apply Islamic religious knowledge to students, a teacher must have an interesting learning method. Interesting learning methods will help students be enthusiastic and active in studying Islamic religious education. Islamic Religious Education is carried out in schools with the aim of fostering faith, piety, and noble character in students. The purpose and function of Islamic religious education in schools is the realization of the ideals of Islamic teachings. To carry out the mission of human welfare in order to become servants of Allah SWT both physically and spiritually in this world and the hereafter. In the Big Indonesian Dictionary it is said that effective means effect, influence, and impression. Effectiveness is how an organization succeeds in obtaining and utilizing resources in an effort to realize operational goals. Effectiveness is related to the implementation of main tasks, achievement of goals and timeliness as well as the active participation of members. The group investigation method is a method that emphasizes group learning that involves students in the learning process. Slavin said the GI learning method is a learning system that involves students working together in groups, so that students know each other's abilities among group members.